Peran Serta Kelompok Wanita Tani dalam Meningkatkan Ekonomi Keluarga dengan Pemanfaatan Lahan Pekarangan Berbasis Green Economy - Firqotus Sa’idah; Nasruddin; Madnasir (SAFE-Network, 2023)
This study aims to analyze the role of women in improving the family economy by utilizing the yard with the green economy concept. The method used in this study is a qualitative method using library analysis tools or library research studies. Library research studies are methods used by researchers to collect data or find out sources related to this topic which can be obtained from various sources such as journals, books, the internet, and other sources. Data obtained by tracing the source of the literature. The results in this study are that the role of women is important in improving the family economy. With the existence of a government program, namely a group of women farmers who can manage unproductive yards to be productive. By cultivating hydroponic plants that help improve the economy and welfare, as well as to have a positive impact on improving the quality of the environment.